Voz e disfunção temporomandibular em professores - Machado, Ilza Maria (2009)
AIM: Verify the presence and possible correlation between vocal alteration and TMD in teachers, based on data from evaluations by speech therapy, otorhinolaryngology, dental and self referred perspectives. JUSTIFICATION: The present research assumed that there may be correlation between voice alteration and TMD. In the presence of such correlation, activities that involve health promotion and alteration prevention, related to both voice and TMD, will help teachers improve their health conditions and consequently, their working conditions. METHOD: The cross-section study researched 29 teachers of elementary and middle public schools in the city of Sorocaba, in the State of São Paulo, Brazil. It was developed by a multi-disciplinary team composed of one medical doctor (otorhinolaryngologist), two speech therapists and one dentist (specialized in bucomaxillary surgery). All teachers answered a self-referred survey (adapted from BIANCHINI 2000 and FERREIRA et al. 2007), which presented questions aiming at identifying the problem, aspects related to vocal alterations and complaints linked to TMD. This was followed by four evaluations: one to assess vocal quality (auditory perceptive evaluation), a larynx exam (video nasal laryngoscopy) e one related to orofacial and odontological kinesiology. Teachers who presented three or more signs or symptoms identified in the survey, in the orofacial and, in the odontological kinetics evaluations were considered as having voice alterations. During the statistical analysis, the research used the Fisher exact test and the Kappa concordance test. RESULTS: 82,8% of participants self referred to voice alteration and 62.1% to TMD symptoms; 51.7% showed voice alteration during evaluation by an otorhinolaryngologist and 65.5% manifested TMD alteration during evaluation by a dentist. The comparison of evaluation proposals of voice alteration and TMD pointed out to a significant trend to the application of the survey questionnaire. On the other hand, during the correlation and concordance analysis, it was the auditory perceptive evaluation of voice and orofacial kinesiology of TMD (performed by speech therapists) that showed to be significant